Loss of Mismatched HLA Detected in the Peripheral Blood of an AML Patient who Relapsed After Haploidentical Hematopoietic Stem Cell Transplantation - Park, Borae G.; Sohn, Yong-Hak; Oh, Heung-Bum; Seo, Eul-Ju; Jang, Seongsoo; Hong, Sun Pyo (Annals of laboratory medicine, 2015)
KCI Citation Count: 2